2019
DOI: 10.3390/molecules24122219
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Solvent Extraction of Cadmium(II) from Aqueous Chloride Solutions by 2-pyridyl Ketoximes: A Coordination Chemistry Approach

Abstract: The goal of this work is to model the nature of the chemical species [CdCl2(extractant)2] that are formed during the solvent (or liquid-liquid) extraction of the toxic cadmium(II) from chloride-containing aqueous media using hydrophobic 2-pyridyl ketoximes as extractants. Our coordination chemistry approach involves the study of the reactions between cadmium(II) chloride dihydrate and phenyl 2-pyridyl ketoxime (phpaoH) in water-containing acetone. The reactions have provided access to complexes [CdCl2(phpaoH)2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Most efficient extractants include chelating or even macrocyclic ligands [ 12 ]. Today, it is firmly established that an effective extractant should [ 14 ]: (a) selectively coordinate to the toxic metal ion having no or very weak affinity for alkali and alkaline metal ions (e.g., Na + , Ca 2+ , etc.) which are present at higher concentrations in waste and natural waters; (b) give somewhat thermodynamically stable complex with the toxic metal ion; (c) have fast kinetics with the metal ion to be extracted; (d) resist hydrolysis; and (e) result in a reversible complexation allowing for the easy and complete recovery of the metal ion without destruction or decomposition of the extractant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most efficient extractants include chelating or even macrocyclic ligands [ 12 ]. Today, it is firmly established that an effective extractant should [ 14 ]: (a) selectively coordinate to the toxic metal ion having no or very weak affinity for alkali and alkaline metal ions (e.g., Na + , Ca 2+ , etc.) which are present at higher concentrations in waste and natural waters; (b) give somewhat thermodynamically stable complex with the toxic metal ion; (c) have fast kinetics with the metal ion to be extracted; (d) resist hydrolysis; and (e) result in a reversible complexation allowing for the easy and complete recovery of the metal ion without destruction or decomposition of the extractant.…”
Section: Introductionmentioning
confidence: 99%
“…In the liquid-liquid extraction of toxic Cd(II), several extractants have been used including EDTA derivatives, organophosphorus compounds, dithiocarbamates, crown ethers, calix[4]arene derivatives, 8-quinolols, pyridine carboxamides and pyridyl oximes [ 12 , 24 ]. The stimulus of the present work and a previous publication from our groups [ 14 ] was an excellent liquid-liquid extraction study of Cd(II) from aqueous chloride solutions using 1-(2-pyridyl)-tridecane-1-one (2PC12), 1-(2-pyridyl)-pentadecane-1-one (2PC14), 1-(4-pyridyl)-tridecane-1-one (4PC12) and 1-(4-pyridyl)-pentadecane-1-one (4PC14) oximes [ 25 ], Figure 1 . We are doing a parenthesis here to mention that 2PC12, among other 2-pyridyl ketoximes, has also been successfully used for the liquid-liquid extraction of copper(II) from aqueous solutions containing Cl − ions [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 and S8, ‡ respectively. The characteristic ν(C aromatic -H) peak appears at ∼3050 cm −1 in both spectra; 11,46,72,75,76 extra peaks at 2918 and 2860 cm −1 in the spectrum of 2 are due to the ν as (CH 3 ) and ν s (CH 3 ) modes, respectively. 46,75 The peak at ∼1620 cm −1 in both spectra is due to the ν(CvN) mode of the Schiff-base linkage; 46,76 the clear splitting of this peak reflects the presence of two types of imine linkages ( protonated and coordinated) in the tetranuclear complexes.…”
Section: Spectroscopic Studiesmentioning
confidence: 90%
“…The latter experimental fact is not unusual. 72,73 Extensive experimental and theoretical studies on complexes with Schiff bases containing a CvN bond (with the carbon atom attached to an aromatic ring) have revealed that a change in the s character of the N lone pair occurs upon coordination or protonation and the s character of the N orbital involved in the CvN bond increases; this change in hybridization leads to a greater CvN stretching constant relative to the free neutral ligands, thus shifting the ν(CvN) vibrational mode to slightly higher wavenumbers. The IR bands at ∼1470, ∼1270 and ∼1030 cm −1 in the spectra of both complexes are assigned 74 to the ν 1 (A 1 )[ν(NvO)], ν 5 (B 2 )[ν as (NO 2 )] and ν 2 (A 1 )[ν s (NO 2 )] vibrations of the bidentate chelating (C 2v ) nitrato group; the separation of the two highestwavenumber stretching bands is ∼200 cm −1 , in agreement with the bidentate character of the coordinated nitrato groups.…”
Section: Spectroscopic Studiesmentioning
confidence: 99%
“…Restricting further discussion to the former family of ligands, the emphasis of our efforts (only selected references from our work are given below) has been on (a) the optical and magnetic properties of the resulting homo- and heterometallic dinuclear [ 18 , 19 , 20 , 21 ] and polynuclear [ 22 , 23 , 24 , 25 , 26 , 27 ] complexes, (b) the metal-mediated/promoted/assisted reactivity of these ligands [ 28 , 29 , 30 ], and (c) the modeling of the solvent extraction of toxic metal ions from aqueous solutions by 2-pyridyl ketoximes [ 31 , 32 ]. A literature survey reveals that a plethora of homometallic complexes of paoH, mepaoH, phpaoH, and ClpaoH ( Figure 1 ), in their neutral or anionic forms, have been prepared and studied with transition [ 22 , 23 , 24 , 25 , 27 , 28 , 29 , 31 , 32 ] and actinide [ 21 ] metal ions. In contrast, with the exception of [LnCl 3 (phpaoH) 3 ] (Ln = Nd [ 33 ], Sm [ 34 ]), such complexes are not known in lanthanide (Ln) chemistry.…”
Section: Introductionmentioning
confidence: 99%